MEDIA PEMBELAJARAN PJOK TERHADAP PENINGKATAN GERAK DASAR LARI DAN LOMPAT PADA SISWA KELAS IV NEGERI BARENG 1 KOTA MALANG - Nur Cahyati, Nunuk; Dudung Ma’ruf Nuris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' fundamental running and jumping skills through the implementation of the traditional games engklek and gobak sodor within Physical Education (PJOK) lessons. The study employed the Classroom Action Research method based on the Kemmis and McTaggart model, conducted over two cycles comprising the stages of planning, acting, observing, and reflecting. The subjects were 28 fourth-grade students (15 boys and 13 girls) from SD Negeri 1 Bareng, Malang City. Data collection techniques included observation, fundamental movement skill tests, documentation, and field notes. Data analysis utilized both quantitative and qualitative descriptive techniques. The results indicate that implementing the traditional games engklek and gobak sodor successfully improved the students' fundamental running and jumping skills. This is evidenced by the increase in the students' average score from 68.21 in the pre-action stage to 75.36 in Cycle I, rising further to 84.11 in Cycle II. The percentage of learning mastery also increased from 46.43% in the pre-action stage to 67.86% in Cycle I, reaching 89.29% in Cycle II. In addition to enhancing motor skills, the use of traditional games improved student participation, learning motivation, and cooperation during lessons. Thus, the traditional games engklek and gobak sodor serve as effective alternative instructional media in Physical Education for improving the fundamental movement skills of elementary school students.